Accidents happen : a novel - Millar, Louise (Emily Bestler Books/Atria, 2013)
On edge because of the accidental deaths of her parents and the murder of her husband, Kate Parker fears for the well-being of herself and her son, and even after she meets Jago, her unease does not abate for long.